Puma / Nurnabilah Athirah Mohd Amizi - Mohd Amizi, Nurnabilah Athirah (2022)
Under the Puma and Cobra Golf brand names, Puma sells boots, clothing, and accessories. The company's most profitable division is footwear. Puma also sells fragrances, eyewear, and watches under its brand name. Puma's department shops, factory branches, and online platforms account for over a fifth of the company's total revenue. The puma company has released one product which is a gaming chair. The first problem regarding their product is the gaming chair is not comfortable for all body sizes. Second of all, there are no armrest and back support for user’s spine. Lastly, it have no wheels to make people easy to move around. Aside from that, there are a few solutions to that challenge, the most important of which are to innovate, conduct research and development, and incorporate improvements into their product to make it perform better. This is due to add locking castel wheels, add an adjustable armrests and back support. All of these solutions are thought to help Puma provide high-quality products for their consumers, allowing them to continue to expand, improve, and gain more in the future.